Antibiotics: to give or not to give - Ismawi, Hidayatul Radziah (Malaysian Integrated Medical Professionals Association, 2023)
Antibiotics are made from antibacterial substances produced by various species of microorganisms (bacteria, fungi, actinomycetes) that suppress growth of other microorganisms. One of the most well-known discoveries was by Alexander Fleming in 1928 when he discovered penicillin.